KAUM INTELEKTUAL DALAM NOVEL LINGKAR TANAH LINGKAR AIR KARYA AHMAD TOHARI (PENDEKATAN HEGEMONI ANTONIO GRAMSCI) - Rostan Rostan; Juanda Juanda; Faisal Faisal (20-87-2496)
Intellectual people in Ahmad Tohari “Lingkar Tanah Lingkar Air” (Antonio Gramchi’s Hegemony Approach”. The aims of the study is to describe the elements of hegemony’s power achievement, namely intellectual community in novel “Lingkar Tanah Lingkar Air” by Ahmad Tohari. This study uses a sociological approach and Antonio Gramsci’s hegemony theory. This study used qualitative descriptive method in analyzing the data. The result shows that the elements of intellectual power hegemony in novel “Lingkar Tanah Lingkar Air” by Ahmad Tohari illustrate the hegemony power of government and army in the from of hegemony power of traditional intellectuals and organic intellectuals